A method for preparing a nano-particle uniform composite spherical metal powder by gas atomization
Patent Information
- Application Number
- CN202611172647.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-30
AI Technical Summary
CN111940723B公开了一种用于3D打印的纳米陶瓷金属复合粉末,采用球磨使微米陶瓷破碎纳米化并包覆金属粉末,再经等离子球化、气流分级制得球形复合粉末,其工艺链长,且纳米相在球磨过程中易团聚
[0012]本发明的有益效果是:本发明采用“一次共雾化—固化成形—二次雾化”的技术路线,先将共雾化所得粉末经粉末包套热等静压和脱包套轧制工艺固化为全致密的合金棒,纳米相在固态致密化与大变形挤压过程中被均匀固定于合金棒内部,然后再通过二次雾化将合金棒重熔破碎,纳米相在重熔液滴内重新均匀分布,最终使纳米/微米级颗粒在单颗粉末内部弥散均匀分布、无宏观偏聚。相较之下,现有一次雾化共雾化工艺(如CN107414091B)中,纳米颗粒与熔滴仅在雾化锥顶碰撞的瞬间接触,熔滴快速凝固使纳米颗粒来不及向熔滴内部迁移,纳米相易偏聚于粉末表层、分布不均,且粉末表面不规整;本发明经二次雾化所得粉末的纳米相分布均匀、表面圆润光滑,可有效避免打印过程中因纳米相表层偏聚而产生的夹杂与气孔缺陷。
Smart Images

Figure CN122999994A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal powder preparation technology, and in particular to a method for preparing uniform composite spherical metal powders of nanoparticles by gas atomization. Background Technology
[0002] Spherical metal powders are the core raw materials for powder metallurgy and additive manufacturing technologies such as selective laser melting (SLM), electron beam melting (EBM), and hot isostatic pressing (HIP). While currently mainstream gas-atomized pure metal powders possess advantages such as high sphericity and low impurity content, pure metal matrices generally suffer from inherent shortcomings such as low hardness, insufficient wear resistance, poor high-temperature strength, and weak creep resistance. These limitations make it difficult to meet the requirements of extreme operating conditions, such as those for aerospace hot-end components. Introducing nano-ceramic particles as reinforcing phases into the metal matrix is an effective way to improve its overall performance.
[0003] Existing methods for preparing nanoparticle composite spherical metal powders via gas atomization mainly include in-situ melt addition and co-atomization with added nanoparticles. CN111940723B discloses a nano-ceramic-metal composite powder for 3D printing, which uses ball milling to break down micron-sized ceramics into nanoparticles and coat them with metal powder, followed by plasma spheroidization and airflow classification to obtain spherical composite powder. This process has a long chain, and the nanophase is prone to agglomeration during ball milling. CN107414091B discloses a preparation system and method for nano-ceramic reinforced titanium alloy powder. The method uses high-pressure argon gas to carry nano-ceramic powder to form a gas curtain, which then collides and recombines with molten metal droplets at the top of an atomizing cone, directly forming powder through a single atomization. However, in this method, the contact between nanoparticles and molten droplets occurs only in a very short instant at the collision at the top of the atomizing cone. The molten droplets then rapidly solidify, and the nanoparticles do not have enough time to fully diffuse and migrate into the interior of the droplets. This results in uneven distribution of the nanophase within individual powder particles, with most particles agglomerated on the powder surface. Furthermore, the collision and recombination cause the powder surface to become irregular and have satellite powder attached. During the printing process, the surface agglomeration and attached nanoparticles easily form inclusions and trap gas, creating pores and affecting the quality of the formed parts.
[0004] Therefore, how to achieve uniform dispersion of nano-reinforcing phases within a single spherical powder while taking into account the sphericity, surface quality, and batch stability of the powder is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] To overcome the above-mentioned shortcomings of existing gas atomization nanocomposite metal powder preparation technology, the technical problem to be solved by the present invention is to provide a method for preparing uniform composite spherical metal powder by gas atomization in which the nano-reinforcing phase is uniformly dispersed and distributed within a single powder particle, without macroscopic agglomeration, and has high sphericity, good surface quality, and high batch stability.
[0006] To address the aforementioned technical problems, this invention provides a method for preparing uniform composite spherical metal powder using gas atomization, comprising the following steps: Step 1, co-atomization of nanoparticles with external carrier gas: Disperse nano-ceramic powder in carrier gas to form nano-aerosol, and let the nano-aerosol enter from the inner channel of the atomization ring and flow coaxially with the main atomizing gas. After being uniformly mixed with the metal melt in the melt breakup zone, nano-composite metal powder is obtained by gas atomization. Step 2, powder-coated hot isostatic pressing: The nanocomposite metal powder obtained in Step 1 is degassed and dried under vacuum, then filled into a metal coating and sealed. Subsequently, it is subjected to hot isostatic pressing densification treatment to obtain a fully dense alloy billet. Step 3, Uncoated Rolled Alloy Bar: Remove the metal cladding from the alloy billet obtained in Step 2, and then hot roll and extrude it into an alloy bar of the target diameter; Step 4, secondary atomization: The alloy rod obtained in step 3 is atomized to obtain nano-composite metal powder. Step 5, airflow classification: The nanocomposite metal powder obtained in step 4 is subjected to airflow classification to remove nano- and / or micro-sized particles attached to the surface of the powder particles, so as to obtain uniform composite spherical metal powder with nanoparticles in the required particle size range.
[0007] Furthermore, in step 1, the nano-ceramic powder is one or more of TiC, TiB2, and Y2O3, and its addition amount is 0.1 to 10 wt% of the metal melt mass; the powder carrier gas pressure of the nano-aerosol is 0.2 to 0.3 MPa, the main atomizing gas pressure is 4 to 7 MPa, and the oxygen content inside the atomizing powder-making equipment is 0.1 to 2 ppm.
[0008] Furthermore, in step 2, the temperature of the hot isostatic pressing densification treatment is 900–960°C, the pressure is 130–180 MPa, and the holding time is 1–4 h.
[0009] Furthermore, in step 3, the outer metal cladding is first peeled off by turning and pickling to remove the surface carburized layer and oxide contamination layer. Then, the billet is heated to 900-1020℃ for hot rolling and extrusion, with an extrusion ratio of not less than 4:1.
[0010] Furthermore, in step 4, the process parameters for the secondary atomization are: atomizing gas pressure 4-7 MPa, melting power 80-100 kW, power frequency 350-400 kHz, nozzle angle 85-95°, and argon gas temperature for atomization 250-300°C.
[0011] Furthermore, in step 5, the airflow classification uses a two-stage classifier wheel, wherein the frequency of the first-stage classifier wheel is 15-20 Hz, the frequency of the second-stage classifier wheel is 38-45 Hz, the oxygen content inside the classifier is 5-20 ppm, and powders with particle sizes in the ranges of 0-15 μm, 15-53 μm, and 53-150 μm are obtained.
[0012] The beneficial effects of this invention are as follows: This invention adopts a technical route of "first-stage co-atomization—curing and forming—second-stage atomization". First, the powder obtained by co-atomization is cured into a fully dense alloy rod through powder-coated hot isostatic pressing and decoating rolling processes. The nanophase is uniformly fixed inside the alloy rod during solid-state densification and large deformation extrusion. Then, the alloy rod is remelted and broken through secondary atomization, and the nanophase is redistributed uniformly within the remelted droplets. Ultimately, the nano / micron-sized particles are uniformly dispersed and distributed within a single powder particle without macroscopic agglomeration. In contrast, in existing single-stage atomization co-atomization processes (such as CN107414091B), the nanoparticles and the molten droplets only come into contact at the moment of collision at the tip of the atomization cone. The rapid solidification of the molten droplets prevents the nanoparticles from migrating into the interior of the droplets. The nanophase is prone to agglomeration on the powder surface, resulting in uneven distribution and an irregular powder surface. The nanophase distribution of the powder obtained by the secondary atomization of this invention is uniform, and the surface is round and smooth, which can effectively avoid inclusions and porosity defects caused by the agglomeration of the nanophase on the surface during the printing process. Attached Figure Description
[0013] Figure 1 This is a process flow diagram of the method of the present invention; Figure 2 This is a scanning electron microscope image of the nanocomposite metal powder obtained in step 1 of Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the uniform composite spherical metal powder obtained in step 4 of Example 1 of the present invention. Figure 4 This is a comparison chart of the properties of 15-53μm metal powders in the embodiments and comparative examples of the present invention. Detailed Implementation
[0014] The invention will be further described below with reference to the accompanying drawings.
[0015] like Figure 1As shown, the present invention provides a method for preparing uniform composite spherical metal powder with nanoparticles by gas atomization. The overall process chain is as follows: co-atomization of nanoparticles with external carrier gas → hot isostatic pressing of powder coating → decoating and rolling of alloy rods → secondary atomization → airflow classification. Its overall working principle is as follows: first, nano-ceramic particles are introduced into the metal powder through co-atomization with external carrier gas, resulting in a nano-composite metal powder with nanoparticles mostly distributed on the surface; then, the composite powder is densified by hot isostatic pressing and rolled into an alloy rod, so that the nano-phase is uniformly solidified inside the alloy; then, the alloy rod is remelted and subjected to secondary atomization, so that the nano-phase is redistributed uniformly within the droplets and spherically shaped; finally, airflow classification removes surface-adhered particles and controls the particle size, resulting in uniform composite spherical metal powder with nanoparticles.
[0016] Step 1 involves co-atomization of nanoparticles with an external carrier gas. Nano-ceramic powder is dispersed in a carrier gas to form a nano-aerosol. The nano-aerosol enters through the inner channel of the atomization ring and coaxially merges with the main atomizing gas. The purpose of the nano-aerosol entering through the inner channel and being coaxially enveloped and merged by the main atomizing gas is twofold: firstly, the nanoparticles unaggregate and achieve sufficient dispersion in the high-speed gas flow; secondly, the coaxial merging allows the nanoparticles to precisely enter the melt fragmentation zone with the gas flow, uniformly mixing with the molten metal and embedding into the droplets during droplet breakage, reducing the outward loss of nanoparticles and improving the composite yield of the nanophase. Nanocomposite metal powder is obtained through gas atomization, at which point the nanoparticles are mostly dispersed on the surface of the composite powder.
[0017] In step 1, the nano-ceramic powder is one or more of TiC, TiB2, and Y2O3. These nano-ceramic particles have high hardness and good thermal stability, and can play a role in dispersion strengthening and grain refinement in the metal matrix. The amount of nano-ceramic powder added is 0.1–10 wt% of the metal melt mass. The preferred method is that if the amount is too low, the number of nano-reinforcing phases is insufficient, and the strengthening effect is not obvious; if the amount is too high, the tendency of nanoparticle agglomeration increases significantly, and it will increase the melt viscosity and deteriorate the atomization and breakup effect. The powder-carrying gas pressure of the nano-aerosol is 0.2–0.3 MPa. The preferred method is that if the powder-carrying gas pressure is too low, the nano-powder delivery is not smooth and the powder delivery rate is unstable; if the powder-carrying gas pressure is too high, it will interfere with the main atomizing gas flow field and affect the stability of melt breakup. The main atomizing gas pressure is 4–7 MPa. The preferred method is that if the pressure is too low, the droplet breakup is insufficient, and the powder particle size is coarse and the sphericity is poor; if the pressure is too high, the fine powder ratio is too high and energy consumption increases. The oxygen content inside the atomizing powder-making equipment is controlled at 0.1 to 2 ppm to prevent the metal melt and high-temperature powder from oxidizing during the atomization process, thus controlling the oxygen content of the powder from the source.
[0018] Step 2 involves powder-coated hot isostatic pressing (HIP). The nanocomposite metal powder obtained in Step 1 is first degassed and dried under vacuum to remove adsorbed gases and moisture from the powder surface, preventing residual gases from forming pores in the billet during HIP. The powder is then packed into a metal casing and sealed, and subjected to HIP densification to obtain a fully dense alloy billet. HIP uses isotropic high pressure to achieve metallurgical bonding of powder particles in a solid state, eliminating interparticle porosity. Densification is carried out at a relatively low temperature, preventing significant growth and coarsening of the nano-reinforcing phase, ensuring good interfacial bonding between the nano-phase and the metal matrix, and avoiding the increase in oxygen content caused by high-temperature sintering. The preferred HIP temperature is 900–960℃. This preference is based on the following reasons: if the temperature is too low, insufficient diffusion between powder particles makes it difficult to achieve full densification; if the temperature is too high, excessive reaction and growth of the nano-reinforcing phase with the matrix will increase the oxygen content. The pressure is 130–180 MPa, and the preferred pressure is as follows: if the pressure is too low, the densification driving force will be insufficient; if the pressure is too high, the equipment requirements will be high and the cost will increase. The holding time is 1–4 h, and the preferred holding time is as follows: if the holding time is too short, densification will be insufficient; if the holding time is too long, production efficiency will be reduced and it may cause coarsening of the nanophase.
[0019] Step 3 involves uncoating and rolling the alloy bar. First, the outer metal cladding is peeled off by turning and pickling to remove the surface carburized and oxide contamination layers, preventing the cladding material and contamination layer from mixing into the melt during subsequent secondary atomization and introducing impurities. Then, the billet is heated to 900–1020°C for hot rolling and extrusion, with an extrusion ratio of not less than 4:1. The purpose of hot rolling and extrusion is to shape the alloy billet into an alloy bar of the target diameter through large deformation processing, while simultaneously breaking down residual pores and interfaces in the dense microstructure, refining the grains, and promoting further homogenization of the nanophase within the alloy. The optimal heating temperature is based on the following: too low a temperature results in high alloy deformation resistance and easy cracking; too high a temperature leads to coarse grains and increased oxidation. An extrusion ratio of not less than 4:1 ensures sufficient deformation to fully break down and refine the microstructure; too low an extrusion ratio results in insufficient homogenization.
[0020] Step 4 involves secondary atomization. The alloy rod obtained in Step 3 is atomized to produce nanocomposite metal powder. Secondary atomization is a key step in achieving uniform nanophase distribution in this invention: after the alloy rod is remelted, the nanophase solidified inside the alloy melts along with the matrix and is uniformly dispersed in the melt. After the melt is atomized and broken into droplets, each droplet contains a diffusely distributed nanophase. Upon solidification, a composite powder is obtained in which the nanoparticles are uniformly distributed within a single powder particle without macroscopic agglomeration. Since the nanophase is uniformly fixed during the alloy rod preparation stage, secondary atomization does not cause sedimentation and stratification due to the density difference between the nanophase and the melt, nor does it embed itself into the surface of the droplets only at the moment of collision, as is the case with primary co-atomization.
[0021] In step 4, the process parameters for the secondary atomization are as follows: atomizing gas pressure 4–7 MPa, the function and preferred method of which are the same as the main atomizing gas pressure in step 1; melting power 80–100 kW, power frequency 350–400 kHz, using an ultra-high frequency melting power supply can improve the superheat during alloy droplet breakage; nozzle angle 85–95°, a large-angle spray disc can prolong the spheroidization time of the droplets before solidification; argon gas temperature for atomization 250–300°C, preheating the argon gas can reduce the solidification cooling rate of the droplets. The synergistic effect of these parameters ensures that the spheroidization time after droplet breakage is shorter than the solidification time, and the droplets are fully spheroidized under surface tension before solidification, resulting in a powder with a sphericity of 0.94–0.95 and a smooth, rounded surface.
[0022] Step 5 is airflow classification. The nanocomposite metal powder obtained in Step 4 is subjected to airflow classification to remove nano- and / or micro-sized particles adhering to the surface of the powder particles, resulting in uniform composite spherical metal powder with nanoparticles within the desired particle size range. Removing surface-adhered particles improves powder flowability and spreading quality, preventing inclusions and pores caused by particle shedding and agglomeration during printing. Airflow classification employs a two-stage classifier wheel. The first-stage classifier wheel has a frequency of 15–20 Hz, and the second-stage classifier wheel has a frequency of 38–45 Hz. The optimal frequency is determined by the following: the classifier wheel frequency determines the cutting particle size; if the frequency is too low, the removal of small surface-adhered particles is incomplete; if the frequency is too high, too much powder within the target particle size range is separated, reducing the yield. By using two-stage classification and adjusting the classifier wheel frequency, the powder particle size distribution can be precisely controlled. The oxygen content inside the classifier is controlled at 5–20 ppm to prevent oxidation of the fine powder during the classification process. Powders with particle sizes ranging from 0 to 15 μm, 15 to 53 μm, and 53 to 150 μm can be obtained through airflow classification. Among them, powders with particle sizes ranging from 15 to 53 μm are suitable for selective laser melting and forming.
[0023] The present invention will be further described below with reference to embodiments and comparative examples.
[0024] Example 1: A method for preparing uniform composite spherical metal powder with nanoparticles by gas atomization, using TC4 titanium alloy as the matrix and TiC nanoparticles as the reinforcing phase, includes the following steps: Step 1, External carrier gas nanoparticle co-atomization: Externally loaded TiC nano-aerosol is introduced through the inner channel of the atomization ring slit. The amount of nanoparticle added is 6 wt% of the metal melt mass. The main atomizing gas pressure is 4 MPa, and the oxygen content inside the atomization powder preparation equipment is 0.3 ppm. This yields a single-atomized TiC nanocomposite TC4 metal powder, the morphology of which is as follows: Figure 2 As shown; Step 2, powder-coated hot isostatic pressing: TiC nanocomposite TC4 metal powder is vacuum degassed and dried, then filled and sealed with metal packaging, and hot isostatic pressing is performed at a temperature of 900℃, a pressure of 150 MPa, and a holding time of 1 h to obtain an alloy billet. Step 3, Uncoated and rolled alloy bar: The outer metal cladding is removed by turning and pickling to remove the surface carburized and oxide contamination layer; the billet is heated to 900℃ and hot rolled and extruded at an extrusion ratio of 4:1 to obtain an alloy bar of the target diameter; Step 4, Secondary Atomization: The alloy rod is atomized with a gas pressure of 6 MPa, a melting power of 86 kW, a power frequency of 365 kHz, a nozzle angle of 90°, and an argon gas temperature of 280°C to obtain nano-TiC composite TC4 metal powder, the morphology of which is as follows. Figure 3 As shown; Step 5, Air Classification: The powder obtained from secondary atomization is passed through an air classifier to remove nano / micron particles adhering to the powder particle surface. The primary classifier wheel frequency is 18 Hz, the secondary classifier wheel frequency is 45 Hz, and the oxygen content inside the classifier is 10 ppm, yielding nano-TiC composite TC4 metal powders with particle sizes in the ranges of 0–15 μm, 15–53 μm, and 53–150 μm. The properties of the powder in the 15–53 μm particle size range are as follows... Figure 4 As shown.
[0025] contrast Figure 2 and Figure 3 It can be seen that the surface of the composite powder obtained by the first atomization in step 1 is covered with a large number of nano / micron-sized particles and the surface is irregular; while after the second atomization in step 4, the surface of the powder particles is round and smooth, and the nano phase is evenly distributed in the powder without macroscopic agglomeration.
[0026] Comparative Example 1: The only difference between this comparative example and Example 1 is that in step 4, the nozzle angle is 36° and the temperature of the argon gas used for atomization is 20°C. The properties of the resulting powder in the 15–53 μm particle size range are as follows: Figure 4 As shown. Comparing Example 1 and Comparative Example 1, it can be seen that increasing the spray disc angle and raising the argon temperature can prolong the droplet spheroidization time and reduce the solidification rate, thereby improving the sphericity and flowability of the powder.
[0027] Comparative Example 2: The only difference between this comparative example and Example 1 is that the frequency of the secondary classifier wheel in step 5 is 48 Hz, and the properties of the resulting powder in the 15–53 μm particle size range are as follows. Figure 4 As shown in the figure. Comparing Example 1 and Comparative Example 2, it can be seen that the particle size distribution of powder in the 15-53 μm particle size range can be controlled by adjusting the frequency of the classifying wheel.
[0028] Using the 15–53 μm nano-TiC composite TC4 metal powder prepared in Example 1, laser selective melting (SLM) was performed on the printed sample. The tensile strength of the sample was 1352 MPa, which is 14.8% higher than the 1178 MPa of the pure SLM-TC4 printed sample; the microhardness was 446 HV, which is 34.7% higher than the 331 HV of the pure SLM-TC4 printed sample. This indicates that the uniform composite spherical metal powder of nanoparticles prepared in this invention has excellent printing performance.
[0029] Example 2: A method for preparing uniform composite spherical metal powder with nanoparticles by gas atomization, using TC4 titanium alloy as the matrix and Y2O3 nanoparticles as the reinforcing phase, includes the following steps: Step 1, co-atomization of nanoparticles with external carrier gas: External Y2O3 nano aerosol is introduced through the inner channel of the atomization ring slit. The amount of nanoparticles added is 1 wt% of the mass of the molten metal. The pressure of the main atomizing gas is 5 MPa and the oxygen content inside the atomization powder making equipment is 0.1 ppm, so as to obtain Y2O3 nano composite TC4 metal powder that is atomized once. Step 2, powder-coated hot isostatic pressing: the Y2O3 nanocomposite TC4 metal powder is vacuum degassed and dried, the metal is filled and sealed, the hot isostatic pressing temperature is 920℃, the pressure is 160 MPa, and the holding time is 2 h to obtain the alloy billet. Step 3, Uncoated and rolled alloy bar: The outer metal cladding is removed by turning and pickling to remove the surface carburized and oxide contamination layer; the billet is heated to 930℃ and hot rolled and extruded at an extrusion ratio of 4.5:1 to obtain an alloy bar with the target diameter; Step 4, secondary atomization: The alloy rod is atomized with atomizing gas pressure of 7 MPa, melting power of 93 kW, power frequency of 382 kHz, nozzle angle of 85°, and argon gas temperature of 250°C to obtain nano Y2O3 composite TC4 metal powder. Step 5, Air Classification: The powder obtained from secondary atomization is passed through an air classifier to remove nano / micron particles adhering to the powder particle surface. The primary classifier wheel frequency is 20 Hz, the secondary classifier wheel frequency is 48 Hz, and the oxygen content inside the classifier is 5 ppm, yielding nano-Y2O3 composite TC4 metal powders with particle sizes in the ranges of 0–15 μm, 15–53 μm, and 53–150 μm. The properties of the powder in the 15–53 μm particle size range are as follows... Figure 4 As shown.
[0030] Laser selective melting was used to form the 15-53 μm nano-Y2O3 composite TC4 metal powder prepared in Example 2. The oxide film thickness of the printed samples under isothermal oxidation conditions of 650℃, 850℃, and 950℃ was 38.6-75.4 μm, which was significantly lower than the 60.2-138.3 μm of the pure SLM-TC4 printed samples. The oxidation weight gain was greatly reduced, indicating that the introduction of Y2O3 nanophase significantly improved the high-temperature oxidation resistance of the printed samples.
[0031] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for preparing uniform composite spherical metal powder with nanoparticles by gas atomization, characterized in that, Includes the following steps: Step 1, co-atomization of nanoparticles with external carrier gas: Disperse nano-ceramic powder in carrier gas to form nano-aerosol, and let the nano-aerosol enter from the inner channel of the atomization ring and flow coaxially with the main atomizing gas. After being uniformly mixed with the metal melt in the melt breakup zone, nano-composite metal powder is obtained by gas atomization. Step 2, powder-coated hot isostatic pressing: The nanocomposite metal powder obtained in Step 1 is degassed and dried under vacuum, then filled into a metal coating and sealed. Subsequently, it is subjected to hot isostatic pressing densification treatment to obtain a fully dense alloy billet. Step 3, Uncoated Rolled Alloy Bar: Remove the metal cladding from the alloy billet obtained in Step 2, and then hot roll and extrude it into an alloy bar of the target diameter; Step 4, secondary atomization: The alloy rod obtained in step 3 is atomized to obtain nano-composite metal powder. Step 5, airflow classification: The nanocomposite metal powder obtained in step 4 is subjected to airflow classification to remove nano- and / or micro-sized particles attached to the surface of the powder particles, so as to obtain uniform composite spherical metal powder with nanoparticles in the required particle size range.
2. The method for preparing uniform composite spherical metal powder by gas atomization according to claim 1, characterized in that, In step 1, the nano-ceramic powder is one or more of TiC, TiB2, and Y2O3, and its addition amount is 0.1 to 10 wt% of the metal melt mass; the powder carrier gas pressure of the nano-aerosol is 0.2 to 0.3 MPa, the main atomizing gas pressure is 4 to 7 MPa, and the oxygen content inside the atomizing powder preparation equipment is 0.1 to 2 ppm.
3. The method for preparing uniform composite spherical metal powder by gas atomization according to claim 1, characterized in that, In step 2, the temperature of the hot isostatic pressing densification treatment is 900–960°C, the pressure is 130–180 MPa, and the holding time is 1–4 h.
4. The method for preparing uniform composite spherical metal powder by gas atomization according to claim 1, characterized in that, In step 3, the outer metal cladding is first peeled off by turning and pickling to remove the surface carburized layer and oxide contamination layer. Then, the billet is heated to 900-1020℃ for hot rolling and extrusion, with an extrusion ratio of not less than 4:
1.
5. The method for preparing uniform composite spherical metal powder by gas atomization according to claim 1, characterized in that, In step 4, the process parameters for the secondary atomization are: atomizing gas pressure 4-7 MPa, melting power 80-100 kW, power frequency 350-400 kHz, nozzle angle 85-95°, and argon gas temperature for atomization 250-300°C.
6. The method for preparing uniform composite spherical metal powder by gas atomization according to claim 1, characterized in that, In step 5, the airflow classification uses a two-stage classifier wheel, where the frequency of the first-stage classifier wheel is 15-20 Hz and the frequency of the second-stage classifier wheel is 38-45 Hz. The oxygen content inside the classifier is 5-20 ppm, resulting in powders with particle sizes in the ranges of 0-15 μm, 15-53 μm, and 53-150 μm.
Citation Information
Patent Citations
A preparation system and method for nano-ceramic reinforced titanium alloy powder
CN107414091B
A nano-ceramic-metal composite powder for 3D printing and its applications
CN111940723B
